2019
DOI: 10.2169/internalmedicine.0872-18
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of a Nationwide Palliative Care Education Program on Lung Cancer Physicians

Abstract: Objective The early integration of palliative care into standard cancer treatment has become a global standard. The Palliative care Emphasis program on symptom management and Assessment for Continuous medical Education (PEACE) has been conducted in Japan, and previous studies have reported that the PEACE workshop was able to improve various palliative care skills of participants. However, whether or not the effects of the program are long-lasting and if the program consequently changed physicians’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Our research also revealed that the difficulties faced by junior physicians were higher than that noted in previous studies. 31–33 Physicians involved in end-of-life care are required to deal with physical, mental, psychosocial, and spiritual suffering of patients. Although communication and pain/symptom management have been recognized as important areas of competency required of residents delivering end-of-life care, junior physicians might face challenges in treating end-of-life patients and difficulties in their clinical practice because they lack experience and knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Our research also revealed that the difficulties faced by junior physicians were higher than that noted in previous studies. 31–33 Physicians involved in end-of-life care are required to deal with physical, mental, psychosocial, and spiritual suffering of patients. Although communication and pain/symptom management have been recognized as important areas of competency required of residents delivering end-of-life care, junior physicians might face challenges in treating end-of-life patients and difficulties in their clinical practice because they lack experience and knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Educating patients, their families, and HCPs on the essential signi cance of PC is an important task. The government has made several efforts to mitigate these issues, such as HCP education and policy awareness activities, and these have yielded attractive results [39][40][41]. However, since the effects of these interventions are not immediate, continuous efforts are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…One speculation relates to board certification curriculum differences between the two studied groups: that for board-certified medical oncologist includes palliative care and end of life care ( 22 ), whereas that for board-certified pulmonologists does not ( 23 ). Indeed, Inoue et al reported the benefits of a nationwide palliative care education program for lung cancer physicians ( 24 ). In corroboration, a study showed that education is very important to achieve integration between oncology and palliative care ( 25 ).…”
Section: Discussionmentioning
confidence: 99%